Penerapan Model Problem Based Learning Untuk Meningkatkan Keaktifan Belajar Peserta Didik Kelas V.A - Indah Dewi Safitri; Siti Dewi Maharani; Vinencia Ika Indralin (CENDEKIAWAN, 2024)
This study aims to provide a comprehensive analysis of the improvement in learning engagement among students with the implementation of the problem-based learning (PBL) model on the IPAS Lesson Eye. This study utilizes a research method known as class action research (PTK), which consists of two learning cycles. His research focused on the number of students in the VA class at SDN 112 Palembang, which amounted to 24. This study's data collection involves the use of observation and documentation approaches during the learning process. For further data analysis, the research uses quantitative descriptive approaches. The findings indicated an increase in student activity markers. In Cycle I, 12 out of the 24 students obtained a learning activity indicator with a 50% percentage. In Cycle II, there was a notable and positive increase. Out of the 24 pupil participants, 21 were able to achieve the learning activity indicator, resulting in a percentage of 87.5%. Thus, it can be inferred that using the problem-based learning (PBL) model can improve students' learning experiences, particularly those in the VA class, when studying the topic of "light features" in the IPAS curriculum..